Isolated bilateral macrodontia of the mandibular second premolars with familial multiple supernumerary teeth: A case report. Issue 2 (August 2017) - Okuno, Akira; Tanaka, Mitsuro
Abstract: Background: Isolated macrodontia is a rare morphological abnormality that can cause malocclusion and malalignment of the dental arch. Only 17 cases of isolated macrodontia of the mandibular second premolars have been reported. We recently experienced an additional case and reported. Case report: Although its etiology remains unknown, the involvement of genetic factors was hypothesized as the patient's father and younger brother each had two supernumerary teeth, and his other teeth were larger than average. Conclusion: The macrodont affects the surrounding area because of its larger size by disturbing the dental alignment and development of adjacent teeth. A treatment strategy is discussed with reference to the reported cases.